IMPLEMENTATION OF INNOVATIONS IN THE CREATIVE ACTIVITY OF FUTURE EDUCATORS - Rakhimova Feruzakhon Mukhammadjonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Create a modern methodology for the activities of preschool educational organizations in accordance with the strategy of action for the further development of the Republic of Uzbekistan, improve state requirements based on a competency-based approach, create educational and methodological complexes of a new generation to improve the processes of activity aimed at their implementation, the use of innovative methods is determined by the level of knowledge and mental development of the teacher. This article outlines some issues of the theoretical basis for improving the system for developing innovative creative activities of future teachers.